Formal rules-in-use on the EU labour market - Szulc- Obłoza, Agnieszka (Research Papers of Wrocław University of Economics, 2018)
The aim of the article is the analysis of rules-in-use on an individual as well aggregated level. The taxonomic method, descriptive analysis and critical literature review is used in the article. The European Union countries have been ordered and grouped according to the set of rules in force on the labour market. For a detail analysis, four countries have been selected, one country from each group. The taxonomy method has been used to rank the countries. Descriptive analysis of particular rules-in-use in selected countries is done. The World Bank data, mainly collected within Doing Business project and Mutual Information System on Social Protection, Social Security Programs Throughout the World as the main source of information are used. The article ends with a summary of rules-in-use of selected countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 509, s. 417-428
Keywords: labour market; rules-in-use; policy; rynek pracy; reguły w użyciu; interwencja